Pengaruh Strategi Pembelajaran Kooperatif Tipe Jigsaw Dan STAD Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa - Puspitasari, Elsa; , Drs. Ariyanto, M.Pd (2017)
This research aims to know the: (1) the influence of cooperative learning strategy type and strategy cooperative learning, Jigsaw type of Student Achievement-Team Divisions (STAD) against the results of the learning of mathematics. (2) the influence of learning motivation of students toward outcome studied mathematics. (3) test the interactions between strategys of cooperative learning, Jigsaw type and strategys of cooperative learning, Student Achievement Team-type Divisions (STAD) against the results of the study of mathematics learning motivation of students. Types of quantitative research with the design of experiments. Research samples taken by Cluster Random Sampling from a population of grade VII SMP N 1 Gatak year 2016/2017 lessons. Data collection techniques with techniques now, tests, and documentation. Prior to analysis, first performed a test of balance, a test of normality, and the test of its homogeneity. Data analysis techniques using variansi analysis of two way cell does not equal to 5% significance level. The results of this research were obtained: (1) there is the influence of the use of cooperative learning strategy against the results of the learning of mathematics. (2) there is the influence of student's motivation level against the results of the learning of mathematics. (3) there is no interaction between the cooperative learning strategy and motivation towards learning outcomes learning math